Analysis of Management Transfer Funds in Katingan District - ., Kristian; Samosir, Delima; ., Miar (KnE Social Sciences, 2020)
Renewal of the government system into regional autonomy has a major impact on the administration of the government system and the scope of performance in the government in Katingan Regency. The Transfer Fund is intended to assist the region in funding the authority to provide services to the public and reduce the imbalance of government funding sources between the center and the regions, as well as to reduce the gap in government funding between regions. The purpose of this study was to determine the role of Central Government transfer funds on capital expenditure for public services in Katingan Regency and analyze the management of transfer funds and their contribution to capital expenditure. The research is descriptive in order to explain how the Transfer Fund is managed by the Regional Financial and Asset Management Agency of Katingan Regency. The results showed that the regional revenue of Katingan Regency originated from Regional Original Revenue (Pendapatan Asli Daerah or PAD), receipts from transfer funds, and other legitimate receipts. Receipt of transfer funds increases from year to year. The average transfer fund allocation that is intended for public services is increasing especially in the fields of health, sanitation infrastructure, markets, agriculture, road infrastructure, environment, assistance for Early Childhood Basic Education (Pendidikan Anak Usia Dini or PAUD), health operational assistance, small and medium scale industries and the allocation of village funds also increased. Keywords: regional revenue, local revenue, transfer funds, public services.